Chemical constituents and cytotoxicity of Aspidistra letreae - Ho, Duc Viet; Hoang, Hanh Nhu Thi; Vo, Khue Minh; Le, Anh Tuan; Nguyen, Hoai Thi (Hue University Journal of Science: Natural Science, 2020)
A phytochemical investigation of whole Aspidistra letreae plants led to the isolation of 2H-chromen-2-one (1), α-tocopherol (2), (E)-phytol (3), asparenydiol (4) and (25S)-spirost-1β,3α,5β-triol (5). Their structures were determined on the basis of NMR spectral evidences and in comparison with the reported data. Of these, asparenydiol (4) was isolated from the genus Aspidistra for the first time. This is also the first report on the separation and structural determination of (25S)-spirost-1β,3α,5β-triol (5) as a pure compound. The methanol extract from the whole plants of Aspidistra letreae exhibits moderate cytotoxicity against the LU-1, HeLa, MDA-MB-231, Hep-G2, and MKN-7 human cancer cell lines with IC50 values ranging from 52.58 ± 3.65 to 64.78 ± 4.89 μg/mL.